2013
DOI: 10.3126/jonmc.v2i1.7670
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Mapping Of Nepalese Calvaria.

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Lillie et al showed the results of study conducted was different from present study due to the age group involved of specified gender and greater sample size. 3 Bhattarai M showed in the conducted study that mean thickness of parietal and occipital bone were inconsistent with present study due to numerous points considered while measuring the thickness; more sample size and all individual above 20 years were considered as candidate. 4 Farzana et al showed in their study that variations were observed with present study because of the difference in age group (18-73 years) of both gender, 1 6 slice CT scan used, and consecutive patient regarded as participant.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Lillie et al showed the results of study conducted was different from present study due to the age group involved of specified gender and greater sample size. 3 Bhattarai M showed in the conducted study that mean thickness of parietal and occipital bone were inconsistent with present study due to numerous points considered while measuring the thickness; more sample size and all individual above 20 years were considered as candidate. 4 Farzana et al showed in their study that variations were observed with present study because of the difference in age group (18-73 years) of both gender, 1 6 slice CT scan used, and consecutive patient regarded as participant.…”
Section: Discussioncontrasting
confidence: 66%
“…Outer and inner table made up of compact bone. 3 There are a few literatures regarding imaging assisted measurement of calvarial thickness among Nepalese population. This study was aimed to measure the thickness of Calvaria and to observe the variation in thickness in between them.…”
Section: Introductionmentioning
confidence: 99%